Features of training of pedagogical staff at the university - Білоус, О. С. (Pedagogy of Higher and Secondary Education, 2012)
Bilous O. S. Features of training of pedagogical staff at the university. The article deals with the problem of teachers’ training specificity at high school as a factor in their professional and creative self-realization.